2004
DOI: 10.1152/jn.00085.2004
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Visually and Memory-Guided Saccades Induced by Electrical Stimulation of the Monkey Frontal Eye Field. II. Suppression of Bilateral Saccades

Abstract: Izawa, Yoshiko, Hisao Suzuki, and Yoshikazu Shinoda. Suppression of visually and memory-guided saccades induced by electrical stimulation of the monkey frontal eye field. II. Suppression of bilateral saccades. J Neurophysiol 92: 2261-2273, 2004; 10.1152/jn.00085.2004. To understand the neural mechanism of fixation, we investigated effects of electrical stimulation of the frontal eye field (FEF) and its vicinity on visually guided (Vsacs) and memory-guided saccades (Msacs) in trained monkeys and found that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…Bilateral RT delays with microstimulation after the Go signal have been reported for structures involved in saccade control, such as the dlPFC (Wegener et al, 2008), FEF (Izawa et al, 2004a), supplementary eye field (SEF) and pre-SMA (Isoda, 2005; Yang et al, 2008), caudate (Watanabe and Munoz, 2010, 2011), and rostral SC (Munoz and Wurtz, 1993b). In cortex, delays were typically stronger for ipsiversive saccades (Izawa et al, 2004b; Isoda, 2005; Wegener et al, 2008), whereas the opposite pattern was observed in SC and caudate (Munoz and Wurtz, 1993b; Watanabe and Munoz, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Bilateral RT delays with microstimulation after the Go signal have been reported for structures involved in saccade control, such as the dlPFC (Wegener et al, 2008), FEF (Izawa et al, 2004a), supplementary eye field (SEF) and pre-SMA (Isoda, 2005; Yang et al, 2008), caudate (Watanabe and Munoz, 2010, 2011), and rostral SC (Munoz and Wurtz, 1993b). In cortex, delays were typically stronger for ipsiversive saccades (Izawa et al, 2004b; Isoda, 2005; Wegener et al, 2008), whereas the opposite pattern was observed in SC and caudate (Munoz and Wurtz, 1993b; Watanabe and Munoz, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…demonstrated the axonal trajectory of single OPNs terminating in the EBN and IBN regions. OPNs discharge tonically during fixation and the tonic excitatory signals are considered to come from fixation neurons in the frontal eye field 39 and indirectly via fixation neurons in the most rostral SC 10–12 …”
Section: Discussionmentioning
confidence: 99%
“…More than one hundred years later, other microstimulation studies evoking eye movements (Robinson and Fuchs, 1969; MacAvoy et al, 1991; Gottlieb et al, 1993; Izawa et al, 2004a,b, 2009), electrophysiological recordings during visual stimulation and/or eye movements (Bizzi, 1968; Wurtz and Mohler, 1976; Bruce and Goldberg, 1985; Segraves and Goldberg, 1987) and studies comparing cells discharge patterns during behavior or its alteration during the stimulation of these same neuronal populations (Bruce et al, 1985; Gottlieb et al, 1994) confirmed the existence of an FEF located in the posterior part of the pre-arcuate sulcus. They distinguished visual (modulated by functional significance), motor and visuo-motor neural populations for saccade, pursuit and fixation/saccade suppression, somehow spatially segregated and with different stimulation thresholds, which depended on the activation state of the monkey at the time of the stimulation.…”
Section: Localization Of Fefmentioning
confidence: 99%
“…A major emphasis has been put on the role of the FEF in the preparation and execution of saccades (Bizzi, 1968; Bruce and Goldberg, 1985). However, FEF also participates in the control of all the other types of eye movements, such as smooth pursuit or optokinetic nystagmus (OKN) (Bizzi, 1968; MacAvoy et al, 1991) and fixation (Izawa et al, 2004a,b, 2009). The intracortical stimulation of several subareas within the FEF is also able to trigger vergence movements (changes of the depth of the gaze) (Crosby et al, 1952, cited by Robinson and Fuchs, 1969).…”
Section: Introduction: Fef a Crossroads For Eye Movements And Visuo-mentioning
confidence: 99%